Hypolipidemic Effects of Allium porrum L. Leaves in Healthy and Streptozotocin-Induced Diabetic Mice - M Eidi; F Soleimani; S Ebrahimi (Institue of Medicinal Plants, ACECR, 2007)
Background: There is evidence about medicinal effects of Allium porrum, Liliaceae (leek) in Iranian traditional medicine. The plant has many properties such as improvement of digestive defects, atherosclerosis, joins pain, respiratory inflammation and kidney stone disease. The hypolipidemic effect of leek is investigated in diabetic rabbit, but its hypoglycaemic effect is unknown yet. Objective: In the present study the hypoglycemic effect of the ethanolic extract of Allium porrum L. (Leek) leaves was investigated in both normal and streptozotocin-induced diabetic mice. Methods: The animals were made diabetic using by streptozotocin (60 mg/kg, i.p.). The ethanolic extract at doses 100, 200, 250 and 300 mg / kg, i.p. were administered for 14 days intraperitoneally. Blood samples were obtained from heart after 14 days. The healthy and diabetic control groups were administered saline as vehicle of extract. Serum glucose and insulin levels were measured by glucose oxidase and radioimmunoassay methods, respectively. Results: The results showed that the ethanolic extract of leek significantly reduced the serum glucose in streptozotocin-induced diabetic mice but not in healthy mice. Also, the ethanolic extract increased serum insulin in diabetic mice. LD50 of ethanolic extract was measured 3500 mg/kg. Conclusion: The present data indicates that extract of leek has hypoglycaemic effect on diabetic animals by releasing insulin from pancreatic beta cells. So, this plant should be considered in future therapeutic researches.